Prevalence and psycho-social factors associated with alcohol use among primary school-going children aged 6 to 13 years in Mbale district, Uganda: a cross-sectional study - Joyce Sserunjogi Nalugya; Noeline Nakasujja; Ingunn M. S. Engebretsen; Catherine Abbo; James K. Tumwine; Seggane Musisi; Juliet N. Babirye; Etheldreda Nakimuli Mpungu; Grace Ndeezi (BMC, 2024)
Abstract Background Alcohol use among children in low-resource settings has received limited attention. This study investigated the prevalence of and biopsychosocial factors associated with alcohol use among children aged 6 to 13 years enrolled in primary education in Uganda. Methods This cross-sectional study conducted in primary schools within Mbale district, employed stratified random sampling to select 470 child-parent dyads. Screening for child alcohol consumption utilized the validated Ugandan (Lumasaaba) version of the Car, Relax, Alone, Forget, Family/Friends, Trouble (CRAFFT) tool. Alcohol Use Disorder (AUD) was diagnosed using the AUD module of the Mini International Neuropsychiatric Interview for children and adolescents (MINI KID). Logistic regression analysis explored associations between alcohol consumption (CRAFFT cut-off score: 1 or more) and biopsychosocial factors (age, sex, nutrition, family dynamics, socioeconomic indicators, and school environment). Data analysis utilized STATA-17 statistical software. Results The median age of the participants was 11 years, with an interquartile range (IQR) of 9 to 12 years and a male to female ratio of 1:1.3. The screened prevalence of alcohol consumption among the children in the past 12 months was 25.2% (95% CI: 21.4-29.4) and 7.2% (95% CI: 5.1-10.0) were diagnosed with AUD. The study found a comparable prevalence of alcohol use between boys (25.0%, 95% CI: 19.4-31.5) and girls (25.4%, 95% CI: 20.0-31.1). Age-specific variations indicated that early adolescents (10 to 13 years), were more likely to consume alcohol 28.1% (95% CI: 23.5-33.3) compared to pre-adolescent children (6 to 9 years) 17.6% (95% CI: 11.9-25.1) in the past 12 months. Factors associated with alcohol use included single-parent households, lower caregiver education, low socioeconomic status, maternal drinking, food insecurity, under-weight, physical discipline by parents, peer influence, rural school attendance, and the school environment. Conclusion The prevalence of alcohol consumption among children in Mbale district, eastern Uganda was high with one-in-four primary-school-children aged 6 to 13 years consuming alcohol in the past year, and no significant gender differences. It highlights various interconnected factors associated with alcohol use among school-aged children. We recommend awareness campaigns at all levels, stricter implementation of alcohol policies, school prevention programs, and family-focused and socio-economic interventions. Nationwide school surveys should target pre-adolescent alcohol use.